Evaluating the efficacy of visual encounter and automated acoustic survey methods in anuran assemblages of the Yungas Andean forests of Argentina - Boullhesen, Martin (2021)
Identifying adequate methods and tools for biodiversity monitoring is fundamental in ecology and conservation biology. Most of the standardised monitoring techniques involve the presence of the researchers at the survey sites meanwhile, passive acoustic monitoring (PAM) of the diversity of anuran species could be a valid alternative. In this study, we evaluated the effectiveness of the use of PAM as a method for anuran species survey and the use of acoustic indices as proxies for the species diversity and species? calling activity level in three species assemblages along the altitudinal gradient of the Yungas forests in NW Argentina. We collected bioacoustic data at three sites along an altitudinal gradient in the Parque Nacional Calilegua. Complementarily, monthly anuran surveys were carried out with the standard method of Visual Encounter Survey (VES). Our results showed that acoustic surveys using PAM could be a reliable tool to assess the anuran diversity in the complex environments of Andean forests. Also, available acoustic indices such as ACI, ADI, AEI, Bio, H and M, could be reliable tools to reflect the diversity of calling species in forest habitats with different levels of biophony in subtropical regions. Nevertheless, long-term monitoring programs must be coupled with VES to accurately reveal anuran diversity along the altitudinal gradient.